Hak Politik Warga Negara dalam Pemilu: Studi Komparatif Antara Sistem Demokrasi Presidensial dan Parlementer - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Azzahra Salsabila Maharani; Dea Avita Sari; Fachrudin Ubaidilah Al Hakim (International Forum of Researchers and Lecturers, 2025)
Elections are a fundamental element of democratic systems, granting citizens te political right to vote and be elected. This study aims to compare the implementation of citizens’ political right in elections under presidential and parliamentary democracy systems. The research method used is normative/doctrinal/library research. This study analyzes the differences in the exercise of political rights in both systems and their impact on the quality of democracy and citizen participation. The findings indicate that the presidential system allows voters to directly elect the head of state, providing strong legitimacy but posing a risk of political deadlock. In contrast, the parliamentary system emphasizes the election of parliament members, who then determine the head of government, offering flexibility but potentially leading to political instability. This study concludes that both systems have advantages and challenges in ensuring citizens’ political rights. Therefore, mechanisms should be developed to enhance political participation and ensure more democratic and inclusive elections.